Small but mighty: Effects of functional indispensability and processing motives on low-status merger partners’ representativeness and commitment to change. - Rosa, M.; Giessner, S.R.; Guerra, R.; Waldzus, S.; Collins, E. C. (The Portuguese Psychological Association’s VIII Annual Symposium on Organizational Behavior, 2015)
Mergers and acquisitions (M&As) occur often between partners with asymmetric group status. Minority (low-status) merger partners frequently perceive themselves as less prototypical (representative) of the new organization, therefore committing less to change, which influences merger success. Treating M&As as social identity processes, this research focuses on the minority merger partner and examines functional indispensability (instrumental contribution of the ingroup) as a condition for prototypicality perceptions and commitment to change. Moreover, underlying motives for prototypicality judgments are assessed via patterns of information processing. In two Studies (N= 114 and N=267), both functional indispensability and information processing were experimentally manipulated and perceptions of relative ingroup prototypicality as well as commitment to change were measured as dependent variables. Taken together, results showed effects of functional indispensability on relative ingroup prototypicality (H1) that are moderated by heuristic vs systematic information processing (H2), suggesting different processes: efficiency for employees perceiving low indispensability and defense for employees perceiving high indispensability. Moreover, (H3) prototypicality mediates the causal relation between functional indispensability and commitment to change, being the path from functional indispensability to prototypicality moderated by information processing, in line with H1. These findings provide important insights into minority perceptions and suggest better practices for human resource management in corporate restructuring processes, such as mergers.